2013
DOI: 10.1371/journal.pone.0077085
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide Fraction as an Add-On to ACQ-7 for Not Well Controlled Asthma Detection

Abstract: BackgroundThe measurement of fractional nitric oxide concentration in exhaled breath (FeNO), a noninvasive indicator of airway inflammation, remains controversial as a tool to assess asthma control. Guidelines currently limit asthma control assessment to symptom and spirometry based appraisals such as the Asthma Control Questionnaire-7 (ACQ-7). We aimed at determining whether adding FeNO to ACQ-7 improves current asthma clinical control assessment, through enhanced detection of not well controlled asthma.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…79 In a study with older population (ages>65 years), FeNO values were statistically significantly higher in those with uncontrolled asthma than those with controlled/partly controlled (regardless of whether asthma control was determined using GINA control criteria or using ACT with a cutoff of 19). 80 The association between asthma control and FeNO was weakened in patients on ICS as observed in four studies. 79,[81][82][83] In addition, pregnant women who had monthly FeNO measurements showed a weak correlation between FeNO and ACT and wide variation in FeNO values.…”
Section: Kq1b Risk Of Bias Assessment Of Observational Studiesmentioning
confidence: 85%
“…79 In a study with older population (ages>65 years), FeNO values were statistically significantly higher in those with uncontrolled asthma than those with controlled/partly controlled (regardless of whether asthma control was determined using GINA control criteria or using ACT with a cutoff of 19). 80 The association between asthma control and FeNO was weakened in patients on ICS as observed in four studies. 79,[81][82][83] In addition, pregnant women who had monthly FeNO measurements showed a weak correlation between FeNO and ACT and wide variation in FeNO values.…”
Section: Kq1b Risk Of Bias Assessment Of Observational Studiesmentioning
confidence: 85%
“…In a study by Volbeda et al it was shown that asthmatic subjects with well-controlled asthma had lower FeNO levels than the subjects with uncontrolled asthma [29]. In a study including 381 asthmatic subjects, the addition of FeNO to ACQ-7 increased by 14.8% the detectability of not well-controlled asthma upon adjustment of maintenance therapy [30]. In another study evaluating the longitudinal assessment of FeNO and sputum eosinophils, it was shown that both FeNO and sputum eosinophils are useful for titrating treatment in asthmatic patients to achieve better long-term control of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…FeNO which has been primarily related to TH2 inflammation has also been prospectively used to guide asthma treatment, with conflicting results [5,28]. In a study including 381 asthmatic subjects, the addition of FeNO to ACQ-7 increased by 14.8% the detectability of not well-controlled asthma upon adjustment of maintenance therapy [30]. In a study including 381 asthmatic subjects, the addition of FeNO to ACQ-7 increased by 14.8% the detectability of not well-controlled asthma upon adjustment of maintenance therapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this reason, it is suggested to use a combination of FeNO level with other measurements such as spirometry or questionnaire for a complete assessment for the asthma control status in patients with asthma since asthma is a heterogeneous disease [18,19]. In the study of the combination of FeNO and questionnaire related to asthma control, Plaza et al found that the addition of FeNO to ACQ-7 (asthma control questionnaire) increased the detectability of not-well-controlled asthma (compare to using ACQ-7 alone) [20]. In this study, the authors found that the combination of FeNO to ACQ-7 increased the detection of uncontrolled asthma by 14.8% following the maintenance therapy adjustment.…”
Section: Discussionmentioning
confidence: 99%